The ASEAN Intergovernmental Commission's Response on Human Rights to the 2021 Myanmar Crisis - H primawanti; W Dermawan; A M Iqbal (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
This article aims to look at the response and role of the ASEAN Intergovernmental Commission on Human Rights as a human rights organization in ASEAN in the crisis that occurs in Myanmar in 2021. The researcher uses a qualitative research method which is carried out by conducting a literature study in collecting data related to the research. Research results show that AICHR is concerned about all forms of violence and human rights violations that occur in Myanmar. Then AICHR as a human rights organization in ASEAN became an arena for member countries to discuss so that the crisis that occurred in Myanmar was immediately ended. Because the principle of non-intervention held by ASEAN countries makes AICHR unable to take much action. It is hoped that this research can provide knowledge and become a source of reference for other researchers related to the response and role of AICHR in the 2021 Myanmar crisis.